Role of macronutrient intake in the epigenetics of obesity. (28th February 2022) - Patel, Priyadarshni; Babu, Jeganathan Ramesh; Wang, Xu; Geetha, Thangiah
Abstract : Obesity is caused by a combination of hereditary and environmental factors. Despite extensive study, contemporary through diet, exercise, education, surgery, and pharmacological treatments, no effective long-term solution has been found to this epidemic. Over the last decade, there has been a tremendous advancement in understanding the science of epigenetics, as well as a rise in public interest in learning more about the influence of diet and lifestyle choices on the health of an individual. Without affecting the underlying DNA sequence, epigenetic alterations impact gene expression. Previous animal studies have shown a link between the type of diet and expression or suppression of obesity genes, but there are very few human studies that demonstrate the relationship between dietary intake and obesity gene expression. This review highlights the effects of carbohydrates, lipids, and protein intake from the diet on obesity-related genes.